A COMPARISON AND INTEGRATION BETWEEN PRIVATE AND PUBLIC SECTOR THROUGH SUSTAINABLE ECONOMICAL DEVELOPMENT OF THE ROMANIAN RURAL AREAS USING BEE ALGORITHM - GRUIA, George; Gruia, George Cristian (Annals of Spiru Haret University. Economic Series, 2018)
The article is focused on presenting a comparison of the public sector with public administration policies and private sector with economical strategies with the purpose of better integration between the two with case study on the European funds in beekeeping and how by studying the bee behavior we too can develop our society to achieve better results. The scope of the article is to show an overview of the European policies into state members with focus on sustainable economic development of Romanian rural areas. This is part of the authors’ research from the last 10 years with focus on public, economic and social development and represent initial results of their yet not published work.